Portugal’s Estado Novo Regime and Apartheid South Africa: two dictatorships and their diplomatic exchanges - Luís Sargento Freitas (Political Observer, 2019)
This paper intends to analyze the foreign policies and diplomatic exchanges of Portugal’s Estado Novo Regime and Apartheid South Africa. In order to fully research these subjects, a search was made in the Portuguese National Records (Torre do Tombo) and the Portuguese Ministry of Foreign Affairs. After a careful selection of the most important documents that served the purposes of this study, we performed a literature review of the subjects at hand, mainly in (Portuguese) history and international relations. The most important reasons for the proximity of these two foreign policies after World War II are extensively debated, whether militarily, economically and politically. The time-span of this research is from 1945 until 1974, however, several events that occurred before and after these dates shall also be scrutinized.